1980
DOI: 10.1080/03601238009372181
|View full text |Cite
|
Sign up to set email alerts
|

Delayed neurotoxicity of cyanofenphos in chickens

Abstract: Delayed neurotoxic ataxia, similar to that caused by neurotoxic organophosphorous compounds, has been shown to occur in hens after oral administration of Cyanofenphos (O-ethyl-O-Cyanophenyl phenyl phosphonothionate) following either single or repeated oral doses. Axonal and myelin degeneration affecting the long tracts in spinal cord, peripheral nerves and medulla was demonstrated. The distal fibers with large diameters were particularly affected. This finding is a new contribution which has not been previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…This susceptibility of the adult Peking duck to the neurotoxic effect of cyanofenphos is comparable with that of the adult chicken. This suggestion is in agreement with El-Sebae et al (1980), who found that cyanophenphos at 1.5-3 mg/kg'd for 16 d produced neurotoxic signs in adult chickens.…”
Section: Discussionsupporting
confidence: 90%
“…This susceptibility of the adult Peking duck to the neurotoxic effect of cyanofenphos is comparable with that of the adult chicken. This suggestion is in agreement with El-Sebae et al (1980), who found that cyanophenphos at 1.5-3 mg/kg'd for 16 d produced neurotoxic signs in adult chickens.…”
Section: Discussionsupporting
confidence: 90%